Intellectual capital assessment at large Texas banks prior to the pandemic - Vilches Robert, Marcelo; Gahona-Flores, Orlando (Revista Venezolana de Gerencia, 2025)
The present research studies the relationship between Intellectual Capital and Financial Performance in the banking sector in Texas in the United States. The research uses the Intellectual Value Added Coefficient model and its components to measure intellectual capital. Return on Assets and Return on Equity are used to measure financial performance. This quantitative research uses data from the 100 largest Texas banks in 2023, over the period 2015 to 2019. A measurement is defined in the overall pre-pandemic period of COVID-19. Multiple linear regression analysis is the econometric mathematical model chosen to test the hypotheses. In conclusion, the study found a significant positive relationship between the Intellectual Value Added Coefficient, Return on Assets and Return on Equity. In the context of its components, the Capital Employed Efficiency Coefficient shows the most substantial effect on Return on Assets and Return on Equity. Human Capital Efficiency shows a positive statistical relationship with Return on Assets and Return on Equity. Structural capital efficiency shows a positive statistical relationship with Return on Equity, but not Return on Equity.